Fokala mekanismer och seismiska moment tensorer av seismiska händelser i Kirunavaaragruvan (metodologiska- och praktiska aspekter) - Skott, Johan (2013)
With increasing depth of mining in underground mines, the challenges with problems with rock bursts related to seismic events also increase. Seismic monitoring systems are installed in mines for monitoring of the seismic events and better understanding of the cause for them. The data from the monitoring systems are used to study the seismic events and their parameters.Some of the dynamic parameters of the seismic sources – the focal mechanism and the seismic moment tensor can be used to find the type of failure in the seismic source and the fault planes.This study focuses on the analysis of the focal mechanism and moment tensor of the seismic events in and nearby Block 19 in LKAB's mine in Kiruna, Kirunavaara. The aim of the thesis is to find the factors that affect the focal mechanism solutions and moment tensor obtained from the JMTS software (IMS) and to develop recommendations for future use of this software; to obtain solutions for the focal mechanisms and moment tensors and to find some relationship between the results and the available structural geological model.Initial tests of the JMTS software were performed to identify the parameters which impact the focal mechanism solutions. The results from the tests were used to prepare recommendations and rules for further processing of the data to obtain the focal mechanisms and moment tensors.The results for the nodal planes from the focal mechanisms and the double-couple component of moment tensors were analyzed and the dominant orientation of the strike was found to be consistent and around North-South direction. The decomposition of the obtained moment tensors showed a relatively even distribution of shear-related and volume changing mechanisms. Validerat; 20131210 (global_studentproject_submitter)